Abnormal esophageal motility during a solid test meal in systemic sclerosis—detection even in very early disease and association with disease progression. Issue 1 (1st October 2018) - Bütikofer, Simon; Jordan, Suzana; Sauter, Matthias; Hollenstein, Michael; Heinrich, Henriette; Freitas‐Queiroz, Natália; Kuntzen, Thomas; Ang, Daphne; Oberacher, Marcos; Maurer, Britta; Schwizer, Werner; Fox, Mark; et al.
Abstract: Objective: This study assessed whether high‐resolution manometry (HRM) with a test meal can detect clinically relevant, abnormal motility already in very early systemic sclerosis (SSc) and whether this finding is associated with subsequent disease progression. Methods: This prospective, longitudinal cohort study recruited 68 consecutive SSc patients (group #1: 32 established disease (ACR, American College of Rheumatology /EULAR, The European League against Rheumatism 2013 and ACR 1980 criteria fulfilled); group #2: 24 early disease (only ACR/EULAR 2013 fulfilled); group #3: 12 very early disease (clinical expert diagnosis of SSc) and 72 healthy controls. HRM evaluated esophageal motility for water swallows and a solid test meal. Results: Systemic sclerosis patients had less frequent effective esophageal contractions during the test meal compared to healthy controls even in very early disease (0.15, 1.0, 2.1 per minute for groups #1, #2, and #3, vs 2.5 per minute in health; P < 0.001, P < 0.001, and P < 0.0085, respectively). Ineffective motility at HRM was associated with a higher modified Rodnan skin score at baseline. Moreover, at mean 18 (10‐31) months of follow‐up, the presence of ineffective motility at baseline was associated with progression of skin disease ( P = 0.01). Cox proportional hazard regression analysis identified hypotensive peristalsis in the test meal (<15% effective solid swallows) and low distal contractile integral (DCI; <400 mm Hg·cm·s) as predictors for skin aggravation, but not for new organ involvement. Conclusion: Ineffective motility during a test meal is present already in patients with very early SSc. Findings on HRM studies are associated with disease severity at baseline, and low percentage of effective swallows in test meal and low mean DCI are both predictors of skin progression during follow‐up. Abstract : Using a standardised test meal we provide evidence, that even in patient with very early disease, esophageal function is impaired. Impaired esophageal peristalsis in the test meal was found to be a predictor of disease progression.